Marine Heatwave Stress Test of Ecosystem-Based Fisheries Management in the Gulf of Alaska Pacific Cod Fishery - Barbeaux, Steven J.; Holsman, Kirstin; Zador, Stephani (Frontiers in Marine Science, 2020)
In 2014–2016 an unprecedented warming event in the North Pacific Ocean triggered changes in ecosystem of the Gulf of Alaska (GOA) impacting fisheries management. The marine heatwave was noteworthy in its geographical extent, depth range, and persistence, with evidence of shifts in species distribution and reduced productivity. In 2017 groundfish survey indicated that GOA Pacific cod (Gadus macrocephalus) had experienced a 71% decline in abundance from the previous 2015 survey. The GOA Pacific cod fishery supports a $103 million fishery which is 29% of the groundfish harvest value in the GOA. In this paper, we demonstrate that an increase in metabolic demand during this extended marine heatwave as well as a reduced prey supply can explain the decline in GOA Pacific cod biomass. Although increased mortality likely led to the decline in the Pacific cod population, historically low recruitment concurrent with the heatwave portends a slow recovery for the stock and gives a preview of impacts facing this region due to climate change. We evaluate the intersection of climate change with ecosystem-based fisheries management in the context of GOA Pacific cod with a description of the sensitivities of the ecosystem, how the changes in the ecosystem affected the Pacific cod stock, and a description of how the management system in the North Pacific handled this shock. We also provide suggestions on how fisheries management systems could be improved to better contend with the impacts of climate change such as the effects of heatwaves like that experienced in 2014–2016.